The inert doublet model in the light of Fermi-LAT gamma-ray data: a global fit analysis - Benedikt Eiteneuer; Andreas Goudelis; Jan Heisig (European Physical Journal C: Particles and Fields, 2017)
Abstract We perform a global fit within the inert doublet model taking into account experimental observables from colliders, direct and indirect dark matter searches and theoretical constraints. In particular, we consider recent results from searches for dark matter annihilation-induced gamma-rays in dwarf spheroidal galaxies and relax the assumption that the inert doublet model should account for the entire dark matter in the Universe. We, moreover, study in how far the model is compatible with a possible dark matter explanation of the so-called Galactic center excess. We find two distinct parameter space regions that are consistent with existing constraints and can simultaneously explain the excess: One with dark matter masses near the Higgs resonance and one around 72 GeV where dark matter annihilates predominantly into pairs of virtual electroweak gauge bosons via the four-vertex arising from the inert doublet’s kinetic term. We briefly discuss future prospects to probe these scenarios.